Islam dan Demokrasi: Pesrpektif Tafsir Maudhu’i - Muzayyin, Ahmad; Hidayat, Aleh; Muhyi, Asep Abdul (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This research aims to explore contemporary issues regarding democracy in the context of the Al-Qur'an. This research uses a qualitative approach with descriptive methods and Maudhu'i interpretation. The formal object of this research is Al-Qur'an knowledge and contemporary issues, while the material object is verses in the Al-Qur'an related to democracy. Democracy in the Qur'an is considered something important and principled because democracy is a form of deliberation that produces agreement or consensus. The Qur'an has explained the principles that must exist in democracy, as contained in the letters ash-Syuara', an-Nahl, al-Hujurat, and an-Nisa'. These principles are in line with the principles of democracy in Indonesian state law, known by the acronym "luberjurdil" (direct, general, free, confidential, honest and fair). The qualitative approach in this research is based on secondary data sources, including literature related to the research topic, such as journal articles, books and other sources.